Woolly hair nevus arising on a verrucous epidermal nevus, with controlateral persistent pupillary membrane. - Phiske, MM; Sawalka, SS; Ovhal, AG; Jerajani, HR (European Journal of Pediatric Dermatology, 2006)
Woolly hair nevus is a rare non hereditary condition, seen as a patch of unruly, very curly hair, arising in a field of otherwise unremarkable scalp hair. Most cases have been recognized during the first few months of life, but some have appeared in young adulthood. The cause of the disorder is unknown. In 50 % of cases, it coexists with linear verrucous epidermal nevus elsewhere on the skin, generally seen on the same side of the body as woolly hair nevus and commonly involving neck, shoulder or arm. Except for ocular abnormalities, no systemic disorders are associated with this condition. A case of woolly hair nevus with ipsilateral epidermal nevus and contralateral persistent pupillary membrane is here reported.